Strategic Use of Women’s Language Features in Jennifer Parlamis’ TED Talk - Qutratu'ain, Dita Shafa; Latifah, Nur (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2026)
Recent studies have shown that women's language features (WLF) increasingly function as rhetorical strategies in professional discourse rather than mere gender markers, yet research in globally mediated speaking contexts such as TED Talks remains limited. This study aims to examine the types of WLF used in Jennifer Parlamis' TED Talk entitled